Combined treatment of marizomib and cisplatin modulates cervical cancer growth and invasion and enhances antitumor potential in vitro and in vivo - Zhang, Ziruizhuo; Zhang, Songcheng; Lin, Bingjie; Wang, Qixin; Nie, Xiaojing; Shi, Yonghua (Frontiers in Oncology, 2022)
Proteasome inhibition is an attractive approach for anticancer therapy. Cisplatin (cis-diamminedichloroplatinum cisplatin, CDDP) is widely used as a standard chemotherapy drug in the treatment of solid malignant tumors, such as cervical cancer, ovarian cancer, colorectal cancer, and lung cancer. However, the development of CDDP resistance largely limits its clinical application. Proteasome inhibitors may enhance traditional chemotherapy agent-induced cytotoxicity and apoptosis. Marizomib (NPI-0052, salinosporamide A, Mzb), a second-generation proteasome inhibitor, shows synergistic anticancer activity with some drugs. Currently, the effect of Mzb on cervical cancer cell proliferation remains unclear. In this study, we explored the role of Mzb in three cervical cancer cell lines, HeLa, CaSki, and C33A, representing major molecular subtypes of cervical cancer and xenografts. We found that Mzb alone showed noteworthy cytotoxic effects, and its combination with CDDP resulted in more obvious cytotoxicity and apoptosis in cervical cancer cell lines and xenografts. In order to investigate the mechanism of this effect, we probed whether Mzb had a better antitumor response alone or in combination with CDDP by enhancing CDDP-induced angiopoietin 1 (Ang-1) expression and inhibiting the expression of ‎TEK receptor tyrosine kinase (Tie-2) in the Ang-1/Tie-2 pathway, FMS-like tyrosine kinase 3 ligand (Flt-3L) and stem cell factor (SCF) as identified by a cytokine antibody chip test. The results suggest that Mzb has better antitumor effects on cervical cancer cells and can sensitize cervical cancer cells to CDDP treatment both in vitro and in vivo. Accordingly, we conclude that the combination of CDDP with Mzb produces synergistic anticancer activity and that Mzb might serve as an effective drug in potential combination therapy for cervical cancer patients.